2020
DOI: 10.1088/1361-6633/ab8ab6
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of picokelvin physics

Abstract: The frontier of low-temperature physics has advanced to the mid pico-Kelvin (pK) regime but progress has come to a halt because of the problem of gravity. Ultra cold atoms must be confined in some type of potential energy well: if the depth of the well is less than the energy an atom gains by falling through it, the atom escapes. This article reviews ultra cold atom research, emphasizing the advances that carried the low temperature frontier to 450 pico-Kelvin. We review micro gravity methods for overcoming th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 138 publications
(360 reference statements)
0
6
0
Order By: Relevance
“…In orbital microgravity, however, the temperature drops to 3.3 ± 0.5 μK, significantly lower than the on-ground value in the same experimental setting. As discussed earlier, this observation demonstrates the influence of gravity on the PGC process and indicates that the microgravity environment is an attractive and suitable place for studying cold atom physics [ 35 ]. Further experiments indicated that the temperature remained reasonably consistent during long-term operation, as shown in Fig.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…In orbital microgravity, however, the temperature drops to 3.3 ± 0.5 μK, significantly lower than the on-ground value in the same experimental setting. As discussed earlier, this observation demonstrates the influence of gravity on the PGC process and indicates that the microgravity environment is an attractive and suitable place for studying cold atom physics [ 35 ]. Further experiments indicated that the temperature remained reasonably consistent during long-term operation, as shown in Fig.…”
Section: Resultsmentioning
confidence: 61%
“…A cold atom interferometer operating in microgravity was also demonstrated in a parabolic flight [ 33 ]. In particular, the observation of a BEC in the International Space Station has been reported [ 34 ], and intense on-going efforts have been devoted to sub-nanokelvin physics in the space lab [ 35 ]. Moreover, the cold atom platform in space is believed to have great potential for applications for quantum sensing and fundamental physics, and several promising proposals have been suggested, including the detection of gravitational waves and search for dark matter [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of ultracold-atom physics as platforms for chip-based matter wave manipulation [1], high-accuracy time keeping systems [2,3], quantum computing and simulation [4][5][6][7] is an active research field. Understanding atom-surface interactions is essential for achieving near-surface atom trapping, as required for the operation of micro-fabricated atom chips.…”
Section: Introductionmentioning
confidence: 99%
“…China is scheduled to launch the space station experimental module by the end of 2022, which will be equipped with a Cold Atom Physics Rack (CAPR). The atomic deep cooling adopts the two-stage cooling (TSC) scheme proposed by Peking University [24][25][26][27]. In the first stage, atoms undergo the runaway evaporation cooling process in an optical trap formed by two crossed laser beams with narrow beam diameter and high power.…”
Section: Introductionmentioning
confidence: 99%